Sistem Pendukung Keputusan Pemilihan Pengobatan Tradisional Kardivaskular Dengan Metode SAW - Rahmad Aditiya; Samsir; Reagan Surbakti Saragih (LPPM Universitas Potensi Utama, 2026)
Cardiovascular disease is one of the leading causes of death worldwide and requires appropriate treatment and therapy selection. In addition to conventional medical treatment, traditional herbal medicine is widely used as an alternative therapy. However, the large number of available herbal remedies often makes it difficult for people to determine the most appropriate option. This study aims to develop a web-based Decision Support System (DSS) to recommend traditional herbal treatments for cardiovascular diseases using the Simple Additive Weighting (SAW) method. The SAW method was implemented through the stages of alternative determination, criteria identification, criteria weighting, decision matrix construction, normalization, preference value calculation, and ranking. The system was developed using PHP and MySQL and evaluated through Black Box Testing. The results indicate that the system is capable of integrating disease data, symptom data, herbal treatment alternatives, and evaluation criteria to generate recommendations based on the highest preference values. Based on the SAW calculation, A1 (Garlic) achieved the highest preference value of 0.94, followed by A5 (0.91) and A7 (0.89), making it the most recommended traditional treatment according to the criteria of treatment effectiveness, cost, side effects, and herbal availability. The system testing results also showed that all major functions operated as expected. Therefore, the SAW method can be effectively applied as a simple, objective, and practical decision-making approach for recommending traditional treatments for cardiovascular diseases.